Biodiversity and Relationship Between Phytoplankton and Aquatic Environment in the Majakerta Coastal Waters, Indramayu, West Java, Indonesia: Keanekaragaman Hayati dan Hubungan Fitoplankton dengan Lingkungan Perairan di Perairan Pesisir Majakerta, Indramayu, Jawa Barat, Indonesia - Happy Widyarini; Sulistiono Sulistiono; Niken T.M. Pratiwi; Ario Damar (Habitus Aquatica, 2022)
Coastal area of Majakerta has a high potential fishery resource and it is commonly utilized by the surrounding community. The fluctuation on the aquatic environment around the coastal area can affect the sustainability of the phytoplankton. Sampling of this study was conducted once in each month at four stations distributed from river to the sea from December 2014 to May 2015, aiming to evaluate biodiversity and relationship between phytoplankton and the aquatic environmental condition in that coastal area. Based on the observation, phytoplankton in Majakerta coastal area consisted of six classes, i.e., Bacillariophyceae (36 genera), Cyanophyceae (7 genera), Dinophyceae (5 genera), Chlorophyceae (4 genera), Zygnemaphyceae (2 genera) and Euglenophyceae (2 genera). Based on the phytoplankton diversity index, it can be inferred that the value is relatively low. There were two habitat groups, namely group 1 (Station 1 and 2; river and estuary) and group 2 (Station 3 and 4; sea), which have influencing parameters: turbidity, pH, and salinity.